Assessing the potential of partial replacing of artemia by practical inert diet in the larviculture of the Amazon River prawn - Maciel, Cristiana Ramalho; Valenti, Wagner Cotroni [UNESP] (Inst Pesca, 2014)
The aim of this study was to evaluate the effect of the replacement of Artemia nauplii by egg-custard in the final phase of Macrabrachium amazonicum hatchery. The treatments were: AN-IX larvae were fed Artemia nauplii during all culture and when they reached stage V, inert diet was added to the feed (control); AN-VII - larvae were fed Artemia nauplii from stage II to stage VI and it was totally replaced by inert diet from stage VII onwards; AN-V - larvae were fed Artemia nauplii from stage II to stage IV and it was totally replaced by inert diet from stage V onwards. Larvae were reared in 120-L culture tanks, coupled to biological filters. Larvae largely ingested inert diet when it was the single food available (90-100% of animals showed digestive tract full). Nonetheless, feeding larvae of M. amazonicum with solely inert diet from stage V or VII onward, negatively affect larval development and survival. Productivity drastically decreased from similar to 60 PL L-1 (control) to similar to 40 PL L-1 in AN-VII and similar to 10 PL L-1 in AN-V. The dry mass of the post-larvae declined similar to 25% in the AN-V and AN-VII. This may be due to low digestibility or nutritional deficiency of the inert diet. Therefore, the complete replacement of Artemia nauplii until stage VII is not recommended for the management of Amazon river prawn larviculture.
Keywords: Macrobrachium amazonicum; egg-custard feeds; prawn larvae